KIPRAH TUAN GURU DALAM POLITIK LOKAL: Studi Peran Politik Tuan Guru di Lombok Tengah - Muhammad Amrillah (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2021)
The character of the master teacher in the Lombok Society Lombok encourages the masters to be more involved in practical politics so that it has an impact on da'wah activities. This study elaborates on the involvement of the master teacher in practical politics and its impact on the preaching of master teachers in Praya District, Central Lombok. This research produces a fact that involvement of master teachers - master teachers in Praya District Central Lombok in politics based on capacity and its role in society, but then the role shifted towards "political oriented"